(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Postoperative sore throat (POST) is a common complication following endotracheal intubation, causing significant patient discomfort. Aim: This study evaluated the efficacy of 2% Xylocaine gel in reducing POST incidence and severity in patients undergoing general anesthesia. Material and Methods: A prospective observational study was conducted on 84 patients (42 intervention , 42 control) at a tertiary care hospital. The intervention group received topical 2% Xylocaine gel prior to intubation, while the control group received standard care without anesthetic gel. POST incidence, severity (measured on a 10-point VAS), time of onset, and duration were assessed postoperatively. The Xylocaine group demonstrated significantly lower POST incidence (16.7% vs 52.4%, p<0.001) and reduced severity (mean VAS 3.1 vs 6.8, p<0.001). Symptom onset was delayed (3 vs 1 hour, p=0.008) and duration shortened (6 vs 12 hours, p=0.003) in the intervention group. Patient-reported effectiveness was high (mean 8.4/10), with no adverse effects observed. Conclusion: Topical 2% Xylocaine gel effectively reduces the incidence, severity, and duration of POST, offering a safe and cost-effective strategy to improve postoperative recovery. These findings support its routine use in clinical anesthesia practice.